The right to tenure security of farmland occupiers in South Africa and Zimbabwe : reviewing the potential impact of expropriation - Nyaradzo, Karubwa (Stellenbosch : Stellenbosch University, 2022)
Thesis (LLM)--Stellenbosch University, 2022.